2004
DOI: 10.1088/0960-1317/14/9/004
|View full text |Cite
|
Sign up to set email alerts
|

Chemical sensing: millimeter size resonant microcantilever performance

Abstract: Based on the use of a resonant cantilever, a mass sensitive gas sensor for the detection of volatile organic compounds (VOC) has been developed. Analyte gases are absorbed by a sensitive layer deposited on the cantilever: the resulting mass change of the system implies the cantilever resonant frequency decreases. In this paper, the process technology, based on the use of SOI wafer, is described. To integrate the measurement, piezoelectric and electromagnetic excitations are investigated and for the detection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 19 publications
3
45
0
Order By: Relevance
“…However, the oscillator configuration case differs significantly from the intrinsic noise case, in that an increase in coating thickness beyond the optimal value may seriously compromise the LOD. This phenomenon has been observed experimentally in [2] and [22].…”
Section: Oscillator Configurationsupporting
confidence: 67%
See 2 more Smart Citations
“…However, the oscillator configuration case differs significantly from the intrinsic noise case, in that an increase in coating thickness beyond the optimal value may seriously compromise the LOD. This phenomenon has been observed experimentally in [2] and [22].…”
Section: Oscillator Configurationsupporting
confidence: 67%
“…According to (15), the sensitivity may be improved by increasing the thickness of the polymeric sensitive coating, provided that [1]. This analytical expression of the sensitivity has been verified experimentally in [7] and [22], which validate the fact that the mass effect is predominant and that the mass increase of the coating is small compared with the coating mass.…”
Section: A Sensor Sensitivitymentioning
confidence: 63%
See 1 more Smart Citation
“…Our results about a decrease and an increase in resonance frequency due to gas ON and OFF are consistent with previous reports of the microcantileverbased gas detection [7][8][9][10].…”
Section: Various Co Concentrations During Air Pump Treatmentsupporting
confidence: 93%
“…In gas detection, several publications have shown that the resonance frequency of MC decreased due to exposure of the gas, such as mercury [6], volatile organic compounds [7], ethanol [8], carbon dioxide [9], freon [10], and water vapor [11]. However, for real sensor applications, the sensor response should be considered in various conditions, such as in higher humidity or vacuum conditions.…”
Section: Introductionmentioning
confidence: 99%